2015
DOI: 10.3390/vetsci3010001
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mammary Carcinomas: A Comparative Analysis of Altered Gene Expression

Abstract: Breast cancer represents the second most frequent neoplasm in humans and sexually intact female dogs after lung and skin cancers, respectively. Many similar features in human and dog cancers including, spontaneous development, clinical presentation, tumor heterogeneity, disease progression and response to conventional therapies have supported development of this comparative model as an alternative to mice. The highly conserved similarities between canine and human genomes are also key to this comparative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 141 publications
(220 reference statements)
2
18
0
Order By: Relevance
“…A comprehensive study done on expression levels of important cellular pathways in canine breast cancer found that cyclin-dependent kinase inhibitors, which regulate the cell cycle, are often dysfunctional. As expected, oncogenic pathways, such as PI3K/AKT, KRAS, MAPK, Wnt, βcatenin, BRCA2, ESR1 and P-cadherin, are upregulated while tumor suppressor pathways, like p53, p16/INK4A (encoded by CDKN2A), PTEN and E-cadherin, are downregulated ( Table 6) [71]. Mutations in any of the genes or proteins involved in these pathways can lead to failure to check important cell events before continuing the cell cycle, which can lead to tumorigenesis.…”
Section: Mammary Gland Tumorssupporting
confidence: 71%
“…A comprehensive study done on expression levels of important cellular pathways in canine breast cancer found that cyclin-dependent kinase inhibitors, which regulate the cell cycle, are often dysfunctional. As expected, oncogenic pathways, such as PI3K/AKT, KRAS, MAPK, Wnt, βcatenin, BRCA2, ESR1 and P-cadherin, are upregulated while tumor suppressor pathways, like p53, p16/INK4A (encoded by CDKN2A), PTEN and E-cadherin, are downregulated ( Table 6) [71]. Mutations in any of the genes or proteins involved in these pathways can lead to failure to check important cell events before continuing the cell cycle, which can lead to tumorigenesis.…”
Section: Mammary Gland Tumorssupporting
confidence: 71%
“…CMTs share many similarities in molecular and clinical features with hBCa . Findings from different studies also suggest that CDK4/6 activity is aberrant in canine mammary tumour (CMT) cells.…”
Section: Introductionsupporting
confidence: 59%
“…CDKs are a family of protein kinases with multiple functions, one of which is to regulate the cell cycle (Figure ) . Specifically, they act as checkpoints and drivers for the smooth transition from one phase to the next.…”
Section: Cdks and Oral Carcinogenesismentioning
confidence: 99%